KANDUNGAN KARBON DI HUTAN RAWA GAMBUT KAWASAN KONSERVASI PT NATIONAL SAGO PRIMA, KEPULAUAN MERANTI, RIAU - Rosalina, Yusi; Kartawinata, Kuswata; Nisyawati, Nisyawati; Nurdin, Erwin; Supriatna, Jatna (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2013)
This study was conducted to collect information regarding carbon storage, particularly the carbon stored in the aboveground biomass as well as in the peat soil. The study site was in a conservation area of the PT National Sago Prima belonging to the PT Sampoerna Agro Tbk. Group. The work was undertaken in January-February 2012. The total aboveground biomass and carbon storage in the research site indicates that the conservation area is a secondary peat swamp forest, with the biomass of 149.18 ton/ha and carbon stock of 70.12 ton C/ha. The aboveground biomass and carbon consisted of biomass and carbon of tree (83.97 ton/ha containing 39.47 ton C/ha, respectively), saplings (20.69 ton/ha containing 9.72 ton C/ha) and seedlings and undergrowth plants (0.03 ton/ha containing 0.01 ton C/ha), wood necromass (24.06 ton/ha containing 11.31 ton C/ha), and litter (20.44 ton/ha containing 9.61 ton C/ha). An allometric equation was developed for Pandanus atrocarpus Griff. providing an estimated total biomass and carbon of 5.16 ton/ha containing 2.42 ton C/ha. The underground C with the mean peat depth of 5.5 m, mean bulk density of 0.18 g/cm3, and the mean organic C of 46.6 % was 464.895,94 ton C/ha. In the entire conservation forest area of 541 ha the total aboveground biomassa and carbon storage was estimated to be 80,708.64 ton and 37,934.00 ton C, while the total underground carbon was 238,96 million MT C.